The Effectiveness of the Snakes and Ladders Game in Improving Knowledge, Attitudes, and Behavior in Preventing Anemia in Adolescent Girls - Prahastuti, Brian Sri; Jumhati, Siti; Kurnia, Ai Lela (Jurnal Kesehatan Masyarakat Perkotaan, 2025)
Anemia among adolescent girls remains a significant public health concern, with a prevalence of 36% in Sukabumi District in 2024. The main contributing factors include iron deficiency, unbalanced dietary patterns, and limited nutritional knowledge. Engaging educational interventions are urgently needed to improve adherence to anemia prevention programs, particularly iron supplementation, free health screenings for adolescents, and the Free Nutritious Meal initiative. This study examined the effectiveness of a modified snakes-and-ladders–based educational game incorporating anemia-related content. A quasi-experimental quantitative design with a two-group pretest–posttest approach was employed, involving 80 adolescent girls in 2025. Data analysis utilized normality testing (skewness), paired t-tests, independent t-tests, and the N-Gain test. The mean knowledge score increased by 2.3 points, attitude score by 3.3 points, and behavior score by 2.4 points. Paired t-test results in the intervention group showed significant improvements in knowledge (p = 0.001), attitudes (p = 0.001), and behaviors (p = 0.001) before and after the intervention. Similarly, the control group demonstrated differences in knowledge (p = 0.001), attitudes (p = 0.001), and behaviors (p = 0.001) over time. Post-intervention independent t-tests indicated significant differences between the intervention and control groups in knowledge (p = 0.001), attitudes (p = 0.001), and behaviors (p = 0.001). The N-Gain analysis revealed an average score of 58,4% (moderately effective) in the intervention group and 23% (ineffective) in the control group. These findings indicate that the educational snakes-and-ladders game is moderately effective in enhancing knowledge, attitudes, and behaviors related to anemia prevention. It is recommended that the Health and Education Offices integrate this game into extracurricular programs and school-based health checks as a complementary strategy to the Free Nutritious Meal initiative.